The Absortion Theory - Mantzuranis, Norberto (2015)
Obesity is classically considered a worldwide epidemic disease and as one of the most important causesof morbid-mortality in many countries.Medical science explains obesity and bases its treatment in the following mathematical equation that enunciatesCalories consumed from food as a consequence of calories expended and calories transformed in fat and stored.This work puts challenged this equation and proposes arguments based on the evolution of the human beings whichincludes the importance of the relation between hunger and satiety.Like in any other endocrine systems, it is proposed the existence of an hypothalamic hormone that regulates thevolume of the adipose tissue through the leptin action.Regulation of the body weight should be based on the equilibrium of the energetic saving capacity, nutrient absorptionand nutrient storage.Our proposal is that the energetic system of abundance regulates the relationship between hunger and satiety; andexplains why slim people that eat large amounts of food do not gain weight, why people that have harmful eatinghabits gain weight and why some people maintain a stable overweight along vast periods of time.Following these precepts it is propose that treatments for obesity should be based on the physiological model thatincludes not only the calories ingested-expended ratio, but also aspects that regulates satiety and modulate the sizeof the adipose tissue as happened with our ancestors.